An embedded software primer - Simon, David E (New Delhi: Pearson, 2013)
About the book: An Embedded Software Primer is a clearly written, insightful manual for engineers interested in writing embedded-system software. The example-driven approach puts you on a fast track to understanding embedded-system programming and applying what you learn to your projects. This book will give you the necessary foundation to work confidently in this field. Building on a basic knowledge of computer programming concepts
Keywords: Computer Science Engineering